2015
DOI: 10.1007/s13196-015-0147-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of growth rate on wood quality of teak (Tectona grandis L. f.): a comparative study of teak grown under differing site quality conditions

Abstract: The present study was carried out to analyse the effect of rate of growth on the wood quality of teak from samples collected from trees which were grown within India as well as from outside. Teak samples (basal discs) from 14 different locations viz. Nilambur, Malayattoor, Konni, Ranni, Vadavar (TN) and Betul (MP) within India and Myanmar, Thailand, Ghana, Benin, Cameroon, Sudan, Tanzania and Trinidad outside India were included in the study. To study the effect of growth rate on wood quality, the collected sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 14 publications
2
10
0
1
Order By: Relevance
“…This result was to be expected, for as the tree ages, the height at which heartwood can be found increases (Yang et al, 1994). Anish et al (2015) agree with the results of this study, indicating that heartwood growth increases with increasing age until reaching a maximum point in the tree height in fast-growth T. grandis plantations.…”
Section: Relationship Between Maximum Heartwood Height and Some Dasomsupporting
confidence: 92%
See 1 more Smart Citation
“…This result was to be expected, for as the tree ages, the height at which heartwood can be found increases (Yang et al, 1994). Anish et al (2015) agree with the results of this study, indicating that heartwood growth increases with increasing age until reaching a maximum point in the tree height in fast-growth T. grandis plantations.…”
Section: Relationship Between Maximum Heartwood Height and Some Dasomsupporting
confidence: 92%
“…For this reason, many studies have investigated heartwood formation during the growth of the tree (Moya et al, 2014). For example, Miranda et al (2011), Kumar and Dhillon (2015), Anish et al (2015), and Galeano et al (2015) observed a decrease in the diameter and proportion of heartwood as the total tree height increases. García et al (2011a and2011b) developed a prediction model that relates the variation of heartwood diameter to total tree height and to the diameter at breast height (DBH) for 2-to 14-year-old plantations of T. grandis.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the presence of heartwood in relatively high proportions in teak makes this species suitable for the wood industry as it gives higher added value (Hegde et al 2014). Due to these desirable features, for many years, research has been focused on the study of the formation, variation and measurements of heartwood in trees growing under fast-growth conditions (Moya et al 2014, Anish et al 2015.…”
Section: Introductionmentioning
confidence: 99%
“…The plants are affected by all of these factors acting whether jointly or independently. Studies show that the sites influence the quality of the wood, modifying its coloration, physical and mechanical properties, as well as its anatomical properties (MOYA et al, 2009;ANISH et al, 2015;RODRIGUEZ-ANDA et al, 2017).…”
Section: Introductionmentioning
confidence: 99%